Regular expressions : pocket primer - Campesato, Oswald (Mercury Learning & Information, 2019)
Packed with realistic examples and numerous commands, this thorough book is intended for data scientists, data analysts, and others who want to understand regular expressions to perform various tasks.
Includes index.
Keywords: Regular expressions (Computer science) -- Handbooks, manuals, etc.; Computer programming -- Handbooks, manuals, etc.; Programming languages (Electronic computers) -- Handbooks, manuals, etc.; elektronické knihy; electronic books